ANALISIS PEMANFAATAN PERPUSTAKAAN SEKOLAH SEBAGAI SUMBER BELAJAR DALAM PEMBELAJARAN PPKN BAGI SISWA KELAS X - Utami, Tri; Noor, Agus Sastrawan; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the use of school libraries as a source of learning for students. The research method used is descriptive with a form of qualitative research. The data source of this study were students of class X MAN 1 Pontianak, PPKn subject teachers, and library staff. Data collection tools are observation sheets, interviews and also documentation with class X MAN 1 Pontianak, PPKn Subject Teachers, and Library Officers. Data analysis uses data reduction, data presentation and conclusions. Test data validity of researchers using data triangulation. The results showed that the MAN 1 Pontianak students had a library that had carried out the functions as they should. Where the library has the functions of educative, informative, creative, and responsibility. In the educational function, teachers and students can use the facilities and library collections as learning and support resources as well as facilitate the learning process. The recreational function is felt by students when they feel bored during class learning, with the existence of various libraries and collections, students feel entertained. The informative function is used by students to seek and develop knowledge apart from the teacher. In addition students are required to take responsibility for borrowed library collections. Keywords:Learning Resources, Library Utilization, PPKn